Facilitators and barriers to medication adherence in an HIV prevention study among men who have sex with men in the iPrEx study in Chiang Mai, Thailand - Arunrat Tangmunkongvorakul (2018)
In 2008, the Pre-exposure Prophylaxis Initiative (iPrEx) study expanded to include men who have sex with men (MSM) in Chiang Mai, Thailand. In full, 114 participants from Chiang Mai joined this international double-blinded trial of daily FTC-TDF (Truvada®) or placebo as a pre-exposure prophylaxis (PrEP) HIV prevention strategy. To better understand the characteristics of iPrEx participants specifically from this underserved population in Thailand, and gain insights into their experiences of trying to take a daily tablet as part of this blinded PrEP trial, we conducted a qualitative study. In 2010, 32 MSM iPrEx participants provided in-depth interviews and an additional 14 joined focus group discussions. Results of the qualitative analyzes suggested that participants held generally positive attitudes toward the iPrEx study and study medication and related this to high rates of adherence to the daily regimen. Participants also reflected on the provision of quality health care as part of participation in the trial, as well as support from clinical research staff, family and friends as helpful in supporting high rates of study medication adherence. Discourse concerning challenges to adherence included medication taking behavior, which was contextualized by lifestyle, living arrangement, social life, social stigma in terms of being mistakenly identified as HIV positive or unintentional disclosure of sexual identity to family and friends, and relationship conflicts with partners. The results provide broader perspectives of participant experiences of the study medication and daily adherence in the larger contexts of the MSM community, close relationships, and the study climate, and can be leveraged in constructing PrEP adherence support approaches within these communities. © 2013 Taylor & Francis.